Implied information adds richness to ‘lean’ media - P.M. Alexander (Communicare)
E-mail has become an accepted means of communication in working environments, and virtual teams who infrequently meet face to face tend to use e-mail extensively even when they are involved in complex and sensitive discussions. This paper reports on an analysis of the e-mails of university students working in virtual teams. It was found that the timing of e-mail messages provides implied information and compensates to some extent for the loss of non-verbal cues that are present in face-to-face communication. This implied information contributes to the richness of the information and assists the reader in interpreting not only the message but also the context. As a result, trust can be established or undermined. Actual examples are provided to illustrate some of the issues.